1965
DOI: 10.1002/art.1780080504
|View full text |Cite
|
Sign up to set email alerts
|

The osteoporosis of rheumatoid arthritis

Abstract: A metabolic bone disturbance has been demonstrated in all of seven patients with classical rheumatoid arthritis of six months to twenty years duration. All patients were receiving salicylate therapy alone while two had received corticosteroids four years before this study.A new quantitative and qualitative histological study of the cytodynamics of bone was used. The evidence suggests that an active diffuse demineralization was present in all patients, and was related directly to the disease process itself or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1966
1966
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…There was no difference between the 2 groups in total osteoid surface. These results differ from those of Duncan et al, who found inactive osteoid seams to be increased in ribs of' patients with RA (19). The systemic trabecular osteopenia found in RA may differ from localized osteopenia in the periarticular trabecular bone.…”
Section: Discussioncontrasting
confidence: 87%
“…There was no difference between the 2 groups in total osteoid surface. These results differ from those of Duncan et al, who found inactive osteoid seams to be increased in ribs of' patients with RA (19). The systemic trabecular osteopenia found in RA may differ from localized osteopenia in the periarticular trabecular bone.…”
Section: Discussioncontrasting
confidence: 87%
“…A similar explanation is sometimes offered to explain the bone loss observed in human rheumatoid arthritis (17).…”
Section: Discussionmentioning
confidence: 89%
“…Eventually the osteoporosis becomes generalized, reflecting a systemic inhibition of osteogenesis. 4 The earliest joint changes in the foot occur at the first, fourth, and fifth metatarsophalangeal joints. 7 The talonavicular joint is often the first tarsal articulation to be involved, although all of the tarsal joints eventually undergo uniform destruction (Fig.…”
Section: Rheumatoid Arthritis Of Adult Onsetmentioning
confidence: 99%